Feasibility Analysis of Essay Test Instruments to Assess Students’ Critical Thinking Skills in Contextual Learning - Qadariah, Nosi; Nengsih, Rodiantifitri; Mairisiska, Titin; Rimin, Rimin; Kurniati, Rahmi; Qalbina, Putri (Universitas Islam Jember, 2026)
This study aims to analyze the feasibility of an essay-based assessment instrument developed to measure university students’ critical thinking skills in a contextual learning setting with local cultural integration. The instrument was constructed based on critical thinking indicators proposed by (Ennis, 2011) and embedded within environmental science content and the Kenduri Sko cultural tradition. Five expert validators assessed the instrument using a validation sheet covering five aspects: content relevance, item construction, language clarity, practicality, and cultural sensitivity. The results show that all aspects received an average score above 3.80, with an overall feasibility percentage of 96.15%, categorized as highly feasible. In addition, qualitative feedback from validators recommended minor revisions in question instructions and refinement of the scoring rubric. Overall, the instrument is considered suitable for use as an authentic assessment tool in culturally contextualized learning in higher education. Further empirical testing and reliability analysis are recommended for broader implementation